Even When No One Is Looking: Students' Perceptions of Social Work Professions. A Case Study in a Northern Ireland University - Denise MacDermott (MDPI AG, 2019)
Public perceptions, increased scrutiny and successive governments’ reshaping and attempting to define what is and what is not social work has eroded the progressive and radical force of the profession. This article explores how students’ perceive the profession and presents evidence from a small-scale study conducted in a Northern Ireland University with 37 undergraduate social work students and 25 postgraduate student social workers (training-as-practice educators) on their perceptions of the characteristics of a professional social worker. A quantitative research design was used, consisting of a face-to-face survey distributed to respondents following an input on the Place Model, (Clarke, 2016). Respondents also shared their perceptions in relation to Freidson’s (2001) three logics: professionalism, bureaucracy and the free market, with Ternary graphs and word clouds used as a novel way to present this data. Several themes emerged as important characteristics of social work professionals including reliability, accountability, ethics and appearance. At the other end of the scale, respondents identified unprofessional, de-personalised and cynical as the least aspirational qualities of the profession.